Evaluation Of Contribution, Effectiveness And Potential Motor Vehicle Tax Against Regional Original Income (PAD) Study In Tax And Retribution Management Agency North Sumatra Province Area Upt Samsat North Medan And South Medan - Nova Febriana; Widia Astuty; Eka Nurmala Sari (SEAN Institute, 2022)
This study aims to determine how much the contribution, effectiveness and potential of the Motor Vehicle Tax to the Regional Original Income (PAD) of North Sumatra Province, especially in UPT Samsat, North Medan and South Medan. This research uses descriptive qualitative method, exploratory research approach of case study by collecting data, taking meaning, and gaining understanding from the case to map an object relatively deeply. The results of the study show: First, the contribution of PKB to PAD for 2021 is 63.06% and is the largest contributor in the Very Good Contribution category, Second, the effectiveness of PKB receipts for North Sumatra Province is 98.88% with Effective Criteria, UPT Samsat Medan Utara is 100.43% with Very Effective criteria, while South Medan is 94.18% with Effective criteria. Third, the number of taxpayers who do not comply with paying their PKB is caused by the awareness factor or the character of the taxpayer, the Covid 19 pandemic, the vehicle is still not paid off at the financing company and the occurrence of traffic accidents. Fourth, the constraints of the South Medan Samsat UPT so that the PKB income has not been achieved, namely economic problems due to the covid 19 pandemic and the lack of awareness of taxpayers about the importance of paying their PKB on time because they feel they do not get direct benefits.